Pengaruh Edukasi Menggunakan Leaflet Terhadap Pengetahuan Tentang Infeksi Masa Nifas Pada Ibu Post Partum Di Puskesmas Lere - Arfiah, Arfiah; Dhanio, Yeyen Wulandari; Sunarti, Sunarti (Akademi Kebidanan Bunga Husada Samarinda, 2024)
Postpartum infection still plays a role as a major cause of maternal death, especially in developing countries such as Indonesia, this problem occurs as a result of midwifery services that are still far from perfect.The purpose of this study was to determine the effect of education using leaflets on knowledge about postpartum infections in postpartum mothers at Puskesmas Lere. This type of research is a descriptive study with a quasi-experimental one group pre and post test approach. The sample in this study was 31 respondents postpartum mothers with total sampling technique. Data collection using a questionnaire sheet. Data analysis used the Wilcoxon statistical test with a significant level of = 0.05. In this study, the results obtained from the one group pre and post test prior to education using leafletsthere are mothers with good and sufficient knowledge each as many as 12 postpartum mothers (38.7%) while mothers with less knowledge as many as 7 postpartum mothers (22.6%) and after education using medialeafletMother's knowledge has increased to 28 postpartum mothers (90.3%) mothers with sufficient knowledge as many as 3 postpartum mothers (9.7%) and there are no postpartum mothers who have less knowledge. The results of data analysis regarding the effect of providing education using leaflets obtained the value ofP-Valueof 0.000 which means the value ofSig < 0.00so that it can be interpreted that there is an effect of providing education using lealet on increasing postpartum mother's knowledge about postpartum infections. The conclusions in this study areproviding education using leaflets has an effect on increasing postpartum mother's knowledge about postpartum infections.